Flow‐induced crystallization of polylactide stereocomplex under pressure. Issue 25 (26th February 2018) - Song, Ying‐Nan; Zhao, Qing‐Xiang; Yang, Shu‐Gui; Ru, Jia‐Feng; Lin, Jian‐Mei; Xu, Jia‐Zhuang; Lei, Jun; Li, Zhong‐Ming
ABSTRACT: Although shear and pressure fields always coexist in practical polymer processing, their combined influence on the crystallization behavior of polylactide stereocomplex (SC) is ambiguous due to the limit of experiment device. In that case, a homemade device was employed to prepare samples under the coexistence of shear and pressure and explore the crystallization behavior of SC. Differential scanning calorimetry and synchrotron radiation were used to investigate the combined effect of shear flow and pressure on SC crystallization. The results show that shear flow was helpful for SC formation. Shear flow promoted the phase mixing of the polymer blends and improved the nucleation efficiency of SC. Pressure had a negative effect on SC formation because of the decrease in free volume. Regard to polylactide homogeneous (HC), pressure played a positive role on HC formation. Pressure suppressed the formation of SC network which could impede HC generation. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46378. Abstract :